Introductory investigation of the Ranque-Hilsch vortex tube as a particle separation device for the PBMR - Burger, Anja (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.